Perancangan Sistem Informasi Pengelolaan Surat Perjalanan Dinas pada Komisi Pemilihan Umum Kab. Kuantan Singingi dengan Bahaasa Pemrograman PHP dan Database MYSQL - Riris Agustin; Billy Hendrik (Universitas Katolik Widya Karya Malang, 2023)
The Kuantan Singingi Regency General Election Commission Office is a government agency that organizes general elections in Indonesia, including members of the DPR/DPD/DPRD, General Elections for President and Vice President as well as General Elections for Regional Heads and Deputy Regional Heads. Design of an information system for managing official travel documents specifically for the Finance Department where the system currently used is still manual. During designing the information system, the methodology used was the first stage, namely Analysis and the second stage, namely Reporting. The aim of this Practical Work Report is expected to be able to help the Kuantan Singingi Regency KPU in improving the existing system, so that the management of official travel documents that have been done manually can be facilitated by the system Application.